KEMAMPUAN AKUMULASI TIMBAL (Pb) PADA AKAR MANGROVE JENIS Avicennia marina (Forsk.) DAN Rhizophora mucronata (Lamk.) DI LAHAN TAMBAK MANGUNHARJO SEMARANG - Titi Wulandari; Rini Budi Hastuti; Endah Dwi Hastuti (Jurnal Akademika Biologi, 2018)
The waters in Mangunharjo are close to industrial activities and human settlements. The high activity in the Mangunharjo area, can flow a variety of waste that can cause pollution, one of which pollution Heavy Metal Pb. This study aims to analyze the ability of roots and leaves Rhizophora mucronata and Avicennia marina in accumulating heavy metal pollutant Lead (Pb). The research was conducted in the pond area of Mangunharjo Subdistrict, Semarang. The design of this research using Randomized Completely Randomized Design 2x1: Factor I namely Type (Avicennia marina and Rhizophora mucronata) at tree stage, Factor II that is root organ with two sampling within 30 days. The research parameters included Pb metal content on mangrove root, and Pb metal content in water and sediment. The result of this research can know the level of Pb metal in water and the environmental sediments of Avicennia marina are 0.36-0,9475 mg / l and 0,941-1,455 mg / kg, respectively. The concentration of Pb metal in water and sediment at the root of Rhizhophora mucronata was 0.175-0,243 mg / l, respectively. Types and Organs do not interact because of their significance of 0.732 (> 0.05). The ability of mangroves to absorb heavy metals in aquatic environments can be determined by calculating Bio Concentration Factors (BCF). BCF values for mangroves Avicennia marina and Rhizophora mucronata ranged from 0.0566 to 0.1068, with the highest values at the root Rhizophora mucronata (0.2879-0.0638). Keywords: Accumulation, Avicennia marina, Rhizophora mucronata, Bio Concentration Factor, significance